Perancangan Sistem Pakar Diagnosa Penyakit Leukemia Dengan Metode Forward Chaining - Yang, Melisa (STMIK TIME, 2015)
Leukemia expert system is an expert system that is designed as a tool to diagnose leukemia disease. The method used for conclusions making is Forward Chaining Method. With this expert system, patient could diagnose first, so that the doctor only check the patient with higher possibility of leukemia disease.